2013
DOI: 10.1371/journal.pone.0083306
|View full text |Cite
|
Sign up to set email alerts
|

When, Where and How Osteoporosis-Associated Fractures Occur: An Analysis from the Global Longitudinal Study of Osteoporosis in Women (GLOW)

Abstract: ObjectiveTo examine when, where and how fractures occur in postmenopausal women.MethodsWe analyzed data from the Global Longitudinal Study of Osteoporosis in Women (GLOW), including women aged ≥55 years from the United States of America, Canada, Australia and seven European countries. Women completed questionnaires including fracture data at baseline and years 1, 2 and 3.ResultsAmong 60,393 postmenopausal women, 4122 incident fractures were reported (86% non-hip, non-vertebral [NHNV], 8% presumably clinical ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 22 publications
(22 reference statements)
0
30
0
8
Order By: Relevance
“…Hip fractures occur equally inside or outside the home, whereas other fragility fractures occur somewhat more commonly outside the home. 6 Fractures occur throughout the year evenly with the exception of hip fractures that occur with a slightly higher likelihood in springtime. 6 It has been shown that most patients who sustain a fracture and are more than 65 years old have weakened bone quality from osteoporosis or osteopenia, conditions that are largely untreated and silent until a fracture occurs, although osteoporosis is the most common disease of the bone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hip fractures occur equally inside or outside the home, whereas other fragility fractures occur somewhat more commonly outside the home. 6 Fractures occur throughout the year evenly with the exception of hip fractures that occur with a slightly higher likelihood in springtime. 6 It has been shown that most patients who sustain a fracture and are more than 65 years old have weakened bone quality from osteoporosis or osteopenia, conditions that are largely untreated and silent until a fracture occurs, although osteoporosis is the most common disease of the bone.…”
mentioning
confidence: 99%
“…6 Fractures occur throughout the year evenly with the exception of hip fractures that occur with a slightly higher likelihood in springtime. 6 It has been shown that most patients who sustain a fracture and are more than 65 years old have weakened bone quality from osteoporosis or osteopenia, conditions that are largely untreated and silent until a fracture occurs, although osteoporosis is the most common disease of the bone. 7 Osteoporosis is a metabolic bone disease characterized by low bone mass and microarchitectural deterioration of bone tissue that results in increased bone fragility and a consequent increase in fracture risk.…”
mentioning
confidence: 99%
“…The effect of seasons on hip fracture is under debate. Despite studies reporting seasonal increases in hip fracture (7,17,18), constant seasonal variation was also reported (6). Our study was conducted throughout the year, and the number of fractures were highest in winter.…”
Section: Selected Variable Number (%)mentioning
confidence: 99%
“…Clinical presentation can be quite variable, ranging from asymptomatic bone loss to severe fractures (especially of the femur and radius) caused by falls. 1 Elderly people, particularly women after menopause, are at a greater risk of developing OP. 2 OP treatment includes correction of nutritional deficiencies, particularly of calcium and vitamin D, prescription of medicines 3 and physical exercise.…”
Section: Introductionmentioning
confidence: 99%